A Tri-band Planar Inverted-F Antenna with Complementary Split Ring Resonator and Reactive Impedance Surface for Wireless Application - Jadhav, T.; Deshpande, S. (Engineering, Technology & Applied Science Research, 2022)
In this paper, a compact, tri-band Planar Inverted-F Antenna (PIFA) using Complementary Split Ring Resonator (CSRR) and Reactive Impedance Surface (RIS) is presented for multiband application. The structure of the PIFA consists of a metallic CSRR and 5×6 periodic unit RIS cells, which accomplishes miniaturization and improves bandwidth and multiband. The RIS metamaterial plane lies between two substrates and acts as a loading function, reducing the volume of the antenna. The measured and simulated results are consistent for a manufactured prototype. The overall size of the antenna is 22.71×3.451×1mm. The PIFA shows a tri-band with an S11 < −10dB bandwidth of approximately 17.08% (2.26-2.67GHz), 5.14% (6.85-7.21GHz) and 19.44% (7.44-9.19GHz) under measurement. The antenna radiates a wave in a preset direction with realized gains ranging from 3.21 to 8.1dbi. The CSRR and RIS improve the performance of the antenna for WLAN, C-band, and X-band applications.